Gender digital divide in education 4.0: A systematic literature review of factors and strategies for inclusion - Iris Cristina Peláez‐Sánchez; Carlos Enrique George Reyes; Leonardo David Glasserman‐Morales (Future in Educational Research)
AbstractThe gender digital divide (GDD) is a phenomenon that refers to the inequalities and differences between men and women in accessing the digital ecosystem in various environments, such as the scenarios of Education 4.0. Bridging the GDD in access, use, and appropriation of technologies would promote the digital inclusion in spaces traditionally dominated by men. A systematic literature review was conducted using seven databases, considering Scopus and Web of Science. Through this, the factors with the most significant impact on the widening of this type of gap were identified. The findings suggest that the elements that limit the GDD are (a) access and use of technologies, (b) social barriers, and (c) gender stereotypes and roles. On the other hand, factors that need to be considered for the digital inclusion of women were identified as follows: (a) the mode of interaction with technologies, (b) digital competencies in Education 4.0, (c) the mode of technology‐mediated teaching and learning, (d) digital competencies in the workplace, and (e) digital participation. It is concluded that more digital inclusion strategies are needed to reduce the GDD, thus requiring greater participation from society and universities to achieve digital equity.